2020
DOI: 10.1002/ijgo.13283
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on Brazilian medical residencies in obstetrics and gynecology

Abstract: Male-perpetrated intimate partner violence (IPV) gravely impacts the lives of women, girls, and their families. Approximately 25%-40% of Mexican women who use health services have reported physical, sexual, and/or psychological IPV at some point during their lives. 1 Recent research has positioned reproductive coercion, a behavior that interferes with women's contraceptive and fertility choices, as a form of IPV. 2 While multiple acts of violence and coercion can occur in the same context (e.g., intimate relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 2 publications
(3 reference statements)
1
10
0
4
Order By: Relevance
“…12 Similarly, in this report, 28% of the residents were assigned to work directly with COVID-19 patients, an event that was also experienced in other residency programs in Brazil and is probably related to shortage of medical personnel. 13 Also, in a similar way, many residents described not having adequate training for this kind of work, which is a worrisome fact. Some authors have, however, described potential benefits in surgical training during the pandemic, especially in general surgery, with the increase in open procedures and more opportunities for emergency surgeries being some of them, 14,15 but these advantages do not apply to all specialties, which, in some cases, are mainly based on elective operations, like head and neck surgery.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…12 Similarly, in this report, 28% of the residents were assigned to work directly with COVID-19 patients, an event that was also experienced in other residency programs in Brazil and is probably related to shortage of medical personnel. 13 Also, in a similar way, many residents described not having adequate training for this kind of work, which is a worrisome fact. Some authors have, however, described potential benefits in surgical training during the pandemic, especially in general surgery, with the increase in open procedures and more opportunities for emergency surgeries being some of them, 14,15 but these advantages do not apply to all specialties, which, in some cases, are mainly based on elective operations, like head and neck surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, in this report, 28% of the residents were assigned to work directly with COVID-19 patients, an event that was also experienced in other residency programs in Brazil and is probably related to shortage of medical personnel. 13 Also, in a similar way, many residents described not having adequate training for this kind of work, which is a worrisome fact.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, several studies about effects of the pandemic on residency training have been performed in different countries. Brito et al [8] investigated the status of OG residents in Brazil, and found that nearly a third were assigned to activities not related to their eld of study, around a quarter complained about defective supplies of PPE, and a third had not got instructed about the management of COVID-19 cases. Bitonti et al [9] studied 476 OG residents in Italy and found out that around 6% had tested positive for COVID-19, only 80% had been instructed about preventive protocols, and nearly half had been provided with adequate PPE.…”
Section: Discussionmentioning
confidence: 99%